Influência do perfil térmico de resfriamento em bobina laminada a quente nas propriedades mecânicas de aço dual phase - Jean Viana Bahia (2019)
Dual phase steels have a high propensity to the occurrence of thickness oscillation during cold rolling, which can cause high discard or refusal of the end product. Among other factors, this variation is due to the high sensitivity of the microstructure of the steels to the different cooling rates at different points of the coil after the coiling in the hot rolling, which can generate a heterogeneous microstructure and, consequently, oscillations of mechanical properties. This susceptibility of the microstructure to the cooling profile is pronounced in dual phase steels with additions of Cr and Mo, because these elements delay the beginning of austenite transformation. In order to know the influence of the thermal profile of cooling after the hot rolling in the microstructure of Cr-Mo alloy dual phase steel, in this study the mechanical properties and the microstructure were evaluated in several points of individual wraps of coils processed in different conditions: coiling according to the initial steel design, coiling in bainitic field and coiling at high temperature within the austenitic field. In addition, the influence of the different cooling rates to which a coil is subjected was evaluated by dilatometer tests. It was also evaluated the behavior of the coils obtained industrially under the conditions tested during the cold rolling and performed a thermography monitoring of the coil cooling after the hot rolling. It was found that for this steel the austenite transformation only starts after the coiling and that the low coil cooling rates after hot rolling results in a slow austenite transformation, leaving the formation of the microstructure of the strip more susceptible to variations in the external conditions of the coil. Thickness oscillations occurred in all conditions evaluated. Finally, it has been found that the coil cooling after hot rolling is not uniform. Thus, it is concluded that none of the conditions evaluated would be adequate to obtain a homogeneous microstructure throughout the coil. It is recommended to evaluate alternatives to ensure a more homogeneous coil cooling or a reassessment of steel alloy design.